Konsep Diri dan Hasil Belajar Siswa MAN 1 ACEH TIMUR - Furaida (Program Studi Pendidikan Agama Islam, 2021)
The self-concept is the center of personality which is a real picture of a person's self, both from an individual's understanding of what and who he is so that individuals can understand himself well. Self-concept is very important, because with a positive self-concept, a person will be more confident with all his strengths and weaknesses. This is related to one's ability to use cognitive abilities according to optimal potential. So, self-concept with learning outcomes are related to each other, a close relationship and useful in achieving success. Likewise, students of MAN 1 Aceh Timur who have a positive self-concept will be successful in participating in teaching and learning activities and in their lives. Self-concept is the center of personality which is a real picture of a person, both from an individual's understanding of what and who he is so that individuals can understand himself well. Self-concept is very important, because with a positive self-concept, a person will be more confident with all his strengths and weaknesses. This relates to a person's ability to use cognitive abilities in accordance with optimal potential. For that, it takes motivation and support from parents, family, and the environment so that students have a positive self-concept in seeing themselves. High self-confidence can increase self-confidence in learning, consequently increasing student learning outcomes. Belief in one's ability to pursue every process in teaching and learning activities is an advantage and a necessity in the world of education. With hope, students who have a positive self-concept will be more successful in pursuing the long path of education and also in post-education life.